Experimental and computational assessment of powered-on base flows in a transonic wind tunnel under large blockage conditions - Tsentis, Spyros; Debiasi, Marco; Goulos, Ioannis; Prince, Simon A.; Zmijanovic, Vladeta (Springer, 2026)
Future high-speed propulsion concepts hold great potential for routine space access and sustainable high-speed flight. However, their development still requires extensive research, particularly in understanding the complex base flow aerodynamics during transonic flight, thus requiring detailed experimental testing. Transonic testing and numerical simulations of tunnel-installed, powered-on models still present many challenges and limitations. In this work, a combined experimental and numerical study is carried out, in an attempt to address some of these challenges. The aim is to identify effective approaches based on Reynolds-averaged Navier–Stokes simulations and to assess their accuracy in predicting the mean base flow for a high-speed, powered-on model installed in a transonic tunnel under large blockage conditions. The motivation stems from the high blockage ratios typically encountered in small-scale transonic facilities when testing powered-on models. This environment is challenging to model computationally. Important details related to computational domain, boundary conditions and proper matching of the experimental flow state are discussed. The impact of the blockage and model support on the base flow inside the tunnel, as well as its similarity relative to free-air conditions, are also highlighted. The results show that the proposed modelling approach can capture the flow field with a maximum error in the base pressure which is below 1.6% relative to the experimental measurements. Based on the findings, suitable practices are provided for the combined experimental and numerical analyses of high-speed, powered-on models.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace engineering; RANS; Transonic wind tunnel; Blockage; Pylon interference; High-speed jet; Base flow